2016
DOI: 10.1002/app.43791
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared‐active and pH‐responsive fluorescent polymer‐integrated hybrid graphene oxide nanoparticles for the detection and treatment of cancer

Abstract: Hybrid nanoparticles for theragnosis have great potentiality to bring desire functionalities in one integrated system. The development of bioimaging guided photothermal therapy (PTT) is pivotal in optimizing cytotoxic cancer therapy. We report nearinfrared (NIR)-active and pH-responsive fluorescent, catechol-conjugated, reduced graphene oxide (rGO)-anchored hybrid nanoparticles that can sharply increase the photothermal heat in response to NIR exposure and exhibit pH-dependent fluorescence emission for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Among various fluorophores, boron–dipyrromethenes (Bodipys) (Scheme A), since first reported by Treibs and Kreuzer in 1968, have emerged as a fascinating class of fluorescent dyes in the past few decades due to their excellent photophysical properties including bright fluorescence, narrow emission bandwidth, resistance to photobleaching, and environment insensitivity. Moreover, the rich chemistry of Bodipys also allows a large number of red to near-infrared (NIR) Bodipy derivatives to be constructed to improve tissue penetration depth and signal-to-background ratio and reduce photodamage. , As a result, Bodipys and their red to NIR derivatives have widely been utilized as fluorescent labels and indicators for various bioimaging applications. In addition, due to the high singlet oxygen ( 1 O 2 ) quantum yield, large light–dark toxicity ratios, high photostability, and facile structural modification, the Bodipy-based photosensitizers have been recognized to be the best potential candidates for photodynamic therapy except for conventional porphyrin derivatives. Despite all of these advantages, typical Bodipys and their derivatives, however, are inherently lipophilic and thus have poor water solubility, which often results in the nonfluorescent aggregates in aqueous solution and also seriously limits their bioavailability to cells and tissues. Moreover, the strong lipophilicity also increases their tendency to accumulate into cellular lipophilic components, thereby decreasing the contrast between specific and nonspecific staining and in turn affecting accurate assessment of cellular events of interest . This is why many strategies had to be employed to endow Bodipys with appropriate water solubility, e.g., through addition of hydrophilic groups, such as sulfonates, phosphonates, carbohydrates, and polyethylene glycols, or formation of water-soluble nanoparticles via polymer encapsulation or host–guest interactions. , However, the complex synthesis, reduced sites for further functionalization, decreased cell membrane permeability caused by the attached ionic groups, and possible dye leakage from nanoparticles may make these methods complicated in some cases. In this work, by applying a one-atom B → C replacement strategy to conventional Bodipy scaffolds, we present a new class of cationic fluorescent dyes, i.e., ...…”
Section: Introductionmentioning
confidence: 99%
“…Among various fluorophores, boron–dipyrromethenes (Bodipys) (Scheme A), since first reported by Treibs and Kreuzer in 1968, have emerged as a fascinating class of fluorescent dyes in the past few decades due to their excellent photophysical properties including bright fluorescence, narrow emission bandwidth, resistance to photobleaching, and environment insensitivity. Moreover, the rich chemistry of Bodipys also allows a large number of red to near-infrared (NIR) Bodipy derivatives to be constructed to improve tissue penetration depth and signal-to-background ratio and reduce photodamage. , As a result, Bodipys and their red to NIR derivatives have widely been utilized as fluorescent labels and indicators for various bioimaging applications. In addition, due to the high singlet oxygen ( 1 O 2 ) quantum yield, large light–dark toxicity ratios, high photostability, and facile structural modification, the Bodipy-based photosensitizers have been recognized to be the best potential candidates for photodynamic therapy except for conventional porphyrin derivatives. Despite all of these advantages, typical Bodipys and their derivatives, however, are inherently lipophilic and thus have poor water solubility, which often results in the nonfluorescent aggregates in aqueous solution and also seriously limits their bioavailability to cells and tissues. Moreover, the strong lipophilicity also increases their tendency to accumulate into cellular lipophilic components, thereby decreasing the contrast between specific and nonspecific staining and in turn affecting accurate assessment of cellular events of interest . This is why many strategies had to be employed to endow Bodipys with appropriate water solubility, e.g., through addition of hydrophilic groups, such as sulfonates, phosphonates, carbohydrates, and polyethylene glycols, or formation of water-soluble nanoparticles via polymer encapsulation or host–guest interactions. , However, the complex synthesis, reduced sites for further functionalization, decreased cell membrane permeability caused by the attached ionic groups, and possible dye leakage from nanoparticles may make these methods complicated in some cases. In this work, by applying a one-atom B → C replacement strategy to conventional Bodipy scaffolds, we present a new class of cationic fluorescent dyes, i.e., ...…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CDs have shown to be a unique platform for delivering different therapeutic agents. CDs are widely used for various applications such as chemotherapy, photodynamic therapy (PDT), photothermal therapy (PTT), gene therapy, and radiation therapy. …”
Section: Recent Trends Of Nanomaterials In Cancer Theranosticsmentioning
confidence: 99%
“…This result indicated that photothermal heat with Dox-ICG-loaded-PLGA NPs substantially inhibited tumor growth. 52,53…”
Section: Paper Materials Advancesmentioning
confidence: 99%